The effects of raja banana (Musa acuminata) peel extract on body weight, body mass index, body fat percentage, and visceral fat mass in male rats with obesity - Devina, Kezia Elian; Indarto, Dono; Susilawati, Tri Nugraha; Wiboworini, Budiyanti (Alma Ata University Press, 2024)
Background: Obesity is a risk factor for metabolic syndrome which can increase mortality. Obese sufferers often fail to lose body weight (BW) through non-pharmacological therapy. Obesity synthetic drugs can cause side effects, so natural ingredients are needed as alternative therapies.Objectives: This study aims to determine the effect of raja banana peel extract (RBPE) on BW, body mass index (BMI), body fat percentage (BFP), and visceral fat mass in obese male rats.Methods: The research subjects were 30 male Wistar rats weighing 125-200 g, aged eight weeks. Obesity was induced by being given high-fat high fructose (HFHFr) feed for 28 days. Rats were randomized and divided into five groups: the negative control group (C-) was given standard feed and distilled water, the positive control (C+) was given standard feed and orlistat, treatment 1 (T1), treatment 2 (T2), and treatment 3 (T3). Which were given standard feed and RBPE doses of 200 mg/kgBW/day, 400 mg/kgBW/day, and 800 mg/kgBW/day. Data before and after the induction of obesity were analyzed using paired t-tests. BW, BMI, and visceral fat mass were analyzed using the One-Way Analysis of Variance (ANOVA) and Repeated Measure ANOVA tests. BFP was analyzed using the Kruskal-Wallis test and the Friedman test.Results: RBPE can significantly reduce BW (p=0.026), BMI (p<0.001), and BFP (p<0.001). However, all groups had no significant difference in visceral fat mass (p=0.187). T3 was the group with the lowest average BW, BMI, BFP, and visceral fat mass although the highest weight loss during the intervention period occurred in C+.Conclusions: RBPE has the potential as an alternative therapy for obesity because it can reduce BW, BMI, and BFP. Future studies can investigate the effect of RBPE on other obesity parameters such as lipid profiles.